Reliability of the Brazilian version of the Cambridge Cognitive Examination Revised CAMCOG-R Confiabilidade da versão brasileira do Cambridge Cognitive Examination Revised - CAMCOG-R - Emylucy Martins Paiva Paradela; Claudia de Souza Lopes; Roberto Alves Lourenço (Arquivos de Neuro-Psiquiatria)
The study' goal was to evaluate the reliability of the Cambridge Cognitive Examination Revised-Brazilian version (Br-CAMCOG-R), a neuropsychological battery measuring the global cognitive function. It was applied on 123 elders and retested at a mean interval of 30.7 days; 60 were evaluated by two raters at the same time. The intraclass coefficient for the set of items and for the subscales varied from 0.93 to 0.98. In the retests the agreement was nearly perfect for the set of items. There was no expressive range in the stability of the instrument for sex, age, schooling, or for the presence of dementia. The Cronbach' alpha of the set of items of the test was high (0.89). The Br-CAMCOG-R has obtained a high level of stability with time, agreement among raters, and optimum internal consistency; it can be useful for epidemiological studies and in specialized clinics to evaluate cognitive functions in elders. O objetivo deste estudo foi avaliar a confiabilidade da versão brasileira do Cambridge Cognitive Examination Revised (Br-CAMCOG-R), uma bateria neuropsicológica que mede a função cognitiva global. Ele foi aplicado em 123 idosos e reaplicado no intervalo médio de 30,7 dias; 60 destes idosos foram avaliados por dois aferidores ao mesmo tempo. O coeficiente de correlação intraclasse para o conjunto dos itens do teste assim como das subescalas variou de 0,93 a 0,98. No reteste a concordância foi quase perfeita para o conjunto dos itens. Não houve variação significativa na estabilidade do instrumento entre os sexos, idade, escolaridade ou presença de demência. O alfa de Cronbach para o conjunto dos itens do teste foi alta (0,89). O Br-CAMCOG-R teve altos níveis de estabilidade no tempo, entre os examinadores e ótima consistência interna; pode ser útil em estudos epidemiológicos assim como em clínicas especializadas na avaliação das funções cognitivas dos idosos.